Drilling Fluid Optimization Using Response Surface Methodology - Satiyawira, Bayu; Maulani, Mustamina; Samura, Lisa; Pramadika, Havidh; Nugrahanti, Asri; Rosyidan, Cahaya; Prima, Andry; Arkaan, Muhammad Dzaki; Yanti, Widia (Scientific Contributions Oil and Gas, 2025)
Water-based drilling fluids commonly exhibit rheological degradation under high-temperature, high-pressure (HTHP) conditions, resulting in significant reductions in viscosity, yield point (YP), and gel strength (GS). Previous studies relying on conventional additives such as PAC, CMC, KOH, and NaOH have not fully resolved this issue, particularly in maintaining rheological stability at elevated temperatures. This study addresses this gap by introducing an alkaline polymer as a multifunctional additive intended to replace several conventional components while enhancing thermal resistance. Response Surface Methodology (RSM) with a Box–Behnken design was used to evaluate the combined effects of Carboxymethyl Cellulose (CMC) and alkaline polymer at three temperature levels: 80°F, 150°F, and 250°F. Experimental results show that at 150°F, the optimized formulation consists of 3.5 g CMC and 3.6 g alkaline polymer, yielding a viscosity of 17.64 cP, plastic viscosity of 12.46 cP, and a YP of 7.72 lb/100 ft², representing a substantial improvement compared to the baseline formulations, where YP values decreased significantly with temperature. The optimized mud also demonstrated improved gel strength and consistent filtrate control relative to non-optimized systems. The novelty of this study lies in the use of an alkaline polymer as a single multifunctional substitute for multiple drilling-fluid additives, combined with a multi-temperature RSM optimization framework. The findings provide a simplified, thermally stable drilling-fluid formulation suitable for HTHP environments.